Effect of teriparatide on quality of life in patients with postmenopausal osteoporosis: a retrospective cohort study. Issue 2 (October 2020) - Yang, Tiansong; Feng, Chuwen; Qu, Yuanyuan; Wang, Qingyong; Yang, Yan; Wang, Bo; Sun, Zhongren; Bao, Shengyong
Objective: To evaluate the effect of teriparatide on life quality in patients with postmenopausal osteoporosis. Methods: Patients treated from January 2014 to December 2016 were retrospectively included. Patients were divided into two groups according the treatment received. Those in the teriparatide treatment group were followed up for 24 months, and patients in the control group received calcium supplements and vitamin D. Scores for back pain using a visual analog scale (VAS) and score of the Oswestry Disability Index (ODI) and 36-item Short Form Health Survey of life quality (SF-36) were evaluated at 3, 6, 12, and 24 months and compared between the groups. Results: In total, 126 patients were included in the teriparatide treatment group and 127 in the control group. There were no significant differences between the groups concerning body mass index, bone density, VAS back pain score, ODI, and SF-36 life quality scores at baseline. At 3, 6, 12, and 24 months' follow-up, VAS scores were significantly lower in the treatment group than in controls; ODI and SF-36 scores were significantly higher in the treatment group than in the control group. Conclusion: Teriparatide can significantly decrease pain and increase mobility and life quality in patients with postmenopausal osteoporosis.